From inpatient to outpatient mental health care: protocol for a randomised feasibility trial of a care transition intervention for patients with depression and anxiety (the AMBITION-trial) - Tönnies, Justus; Ayoub-Schreifeldt, Marayah; Schrader, Viola; Hartmann, Mechthild; Wild, Beate; Friederich, Hans-Christoph; Haun, Markus W. (PLOS ONE, 2023)
Introduction Despite guideline recommendations, inpatients with mental health disorders often do not receive appropriate treatment after discharge. This leads to high readmission rates, problems with medication adherence, increased risk of chronicity and suicide, and exclusion from the labour market accompanied by high individual and social costs. The causes are both system-related, such as limited treatment availability, and patient-related, such as ambivalent motivation to continue treatment and lack of information about available treatment options. The aim of this trial is to assess the feasibility of a Care Transition Intervention (CTI) which supports patients in the psychosocial follow-up treatment process after discharge from a psychotherapy ward. Methods and analysis Fifty patients with depression and/or anxiety who are treated as inpatients at a psychotherapy ward will be included and randomised into two groups with a 1:1 ratio. In the intervention group, patients will receive five CTI sessions with a Care Transition Navigator before and after discharge. The sessions will focus on individual patient support including a) identification and tackling of barriers to initiate follow-up treatment, b) reflection on the inpatient stay and individual progress, with focus on the helpful aspects and c) motivation of patients to organise and take up outpatient treatment. Patients in the control group will receive treatment-as-usual during discharge. We will evaluate the following outcomes: effectiveness of recruitment strategies, patient acceptance of randomisation, practicability of implemented workflows, feasibility of data collection, and clinical outcomes.